1988
DOI: 10.3109/00016488809119444
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Root Against Seasickness: A Conctrolled Trial on the Open Sea

Abstract: In a double-blind randomized placebo trial, the effect of the powdered rhizome of ginger (Zingiber officinale) was tested on seasickness. Eighty naval cadets, unaccustomed to sailing in heavy seas reported during voyages on the high seas, symptoms of seasickness every hour for 4 consecutive hours after ingestion of 1 g of the drug or placebo. Ginger root reduced the tendency to vomiting and cold sweating significantly better than placebo did (p less than 0.05). With regard to vomiting, a modified Protection In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(58 citation statements)
references
References 4 publications
2
52
0
3
Order By: Relevance
“…The traditional Chinese herbal remedy ginger reduces symptoms in patients with nausea of pregnancy, motion sickness, and postoperative nausea and vomiting (Grontved et al, 1988;Phillips et al, 1993;Arfeen et al, 1995;Vutyavanich et al, 2001). In physiological testing, ginger increases fasting antral contractions and the gastric motor response to eating (Micklefield et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional Chinese herbal remedy ginger reduces symptoms in patients with nausea of pregnancy, motion sickness, and postoperative nausea and vomiting (Grontved et al, 1988;Phillips et al, 1993;Arfeen et al, 1995;Vutyavanich et al, 2001). In physiological testing, ginger increases fasting antral contractions and the gastric motor response to eating (Micklefield et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Antiemetic actions of ginger have been reported in patients with nausea during pregnancy and in subjects with motion sickness (Grontved et al, 1988;Vutyavanich et al, 2001). Its effectiveness in preventing postoperative nausea and vomiting is uncertain with some studies observing benefits and others showing no effect (Phillips et al, 1993;Arfeen et al, 1995).…”
mentioning
confidence: 99%
“…In addition to these medicinal uses, ginger continues to be valued around the world as an important cooking spice and is believed to help the common cold, flulike symptoms, headaches, and even painful menstrual periods. Today, ginger root is widely used as a digestive aid for mild stomach upset and is commonly recommended by health care professionals to help prevent or treat nausea and vomiting associated with motion sickness, pregnancy, and cancer chemotherapy (Bone et al, 1990;Grontved et al, 1988;Sripramote et al, 2003). Ginger is used as support in inflammatory conditions such as arthritis (Altman et al, 2001), and may even be used in heart disease (Bhandari et al, 1998) or cancer (Katiyar et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Due its spasmolytic actions, the efficacy of ginger against motion or sea sickness was evidenced in several early studies (Grontved et al, 1988;Holtmann et al, 1989;Stewart et al, 1991), as well as it was showed as an antiemetic in nausea and vomiting induced by chemotherapy in a randomized, cross-over and double blind study (Sontakke et al, 2003). In addition to these reports, Geiger (2005) showed that a 5% solution of essential oil of ginger is an effective post-operative nausea and vomiting prevention when administered preoperatively, concurrently with conventional therapies, to general anaesthesia patients at high risk for postoperative nausea and vomiting, with increased patient satisfaction and less expense to patients and hospital.…”
Section: Zingiber Officinale Roscoe Zingiberaceae (Gengibre)mentioning
confidence: 99%